Yield attributes and yield of okra as influenced by cultivars at Sylhet region (Journal of the Bangladesh Agricultural University, 2016)
An experiment was conducted at the field laboratory of Sylhet Agricultural University from May to October 2013 comprising of 8 okra cultivars viz. BARI Dherosh-1 (control), Orka Onamika, Bankim, Durga, JO (Japanese okra)-1, JO-2, JO-3 and JO-4. This study was intended to select the superior okra cultivar(s) based on yield performance in acidic soil conditions. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications and all the cultivars were evaluated in relation to yield and yield attributes. Significant variations were observed in almost all parameters. Results revealed that high yielding cultivars JO-3 and Bankim produced largest fruits, however maximum number of fruits and fruit setting (%) were exhibited by the latter. The cultivars JO-1 and JO-4 showed maximum fruit weight but JO-4 provided highest fruit diameter. The cultivars Bankim followed by JO-3 & JO-4 were evaluated to be promising cultivars at Sylhet regions considering overall performances regarding yield and yield attributes.J. Bangladesh Agril. Univ. 14(1): 13-16, June 2016